2023
DOI: 10.1177/10634266221149970
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Burnout and Supporting Teachers of Students with Emotional and Behavioral Disorders

Abstract: This article will provide a brief reflection on Garwood’s summary of research on special education teacher burnout and fidelity of implementation in delivery of evidence-based behavioral interventions. Subsequently, we provide a conceptual and empirical summary of key issues for supporting teachers of and students with emotional and behavioral disorders (EBDs) through the lens of BEST in CLASS (a Tier 2 intervention supporting teacher’s use of evidence-based practices with students with or at-risk for EBD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Furthermore, teachers may require connections to resources beyond program specific efforts. To illustrate, teachers may connect to mental health resources through conversations with their coach or seek support for implementing practices outside of the targeted program (Granger et al, 2023). Finally, school administrators can play an important, protective role in the organization of classrooms to help support the learning environment by ensuring particularly challenging, potentially external factors, are evenly distributed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, teachers may require connections to resources beyond program specific efforts. To illustrate, teachers may connect to mental health resources through conversations with their coach or seek support for implementing practices outside of the targeted program (Granger et al, 2023). Finally, school administrators can play an important, protective role in the organization of classrooms to help support the learning environment by ensuring particularly challenging, potentially external factors, are evenly distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Granger et al (2021) reported that high levels of classroom adversity increased the likelihood of negative teacher-student interactions with elementary students with and at risk of EBD. Finally, Granger et al (2023) reported a positive relation between teachers' efficacy in instructional strategies and classroom organization quality at low levels of classroom adversity. However, there was a negative relation between teachers' efficacy in instructional strategies and classroom organization quality at high and average levels of classroom adversity.…”
Section: Classroom Adversity and Classroom Qualitymentioning
confidence: 94%
See 1 more Smart Citation